The impact of different atmospheric CO2 concentrations on large scale Miocene temperature signatures - Hossain, A; Knorr, G; Jokat, W; Lohmann, G; Katharina Hochmuth; Gierz, P; Gohl, K; Stepanek, C (2023)
Based on inferences from proxy records the Miocene (23.03–5.33 Ma) was a time of amplified polar warmth compared to today. However, it remains a challenge to simulate a warm Miocene climate and pronounced polar warmth at reconstructed Miocene CO 2 concentrations. Using a state-of-the-art Earth-System-Model, we implement a high-resolution paleobathymetry and simulate Miocene climate at different atmospheric CO 2 concentrations. We estimate global mean surface warming of +3.1 °C relative to the preindustrial at a CO 2 level of 450 ppm. An increase of atmospheric CO 2 from 280–450 ppm provides an individual warming of ∼1.4 °C, which is as strong as all other Miocene forcing contributions combined. Substantial changes in surface albedo are vital to explain Miocene surface warming. Simulated surface temperatures fit well with proxy reconstructions at low- to mid-latitudes. The high latitude cooling bias becomes less pronounced for higher CO 2 . At higher CO 2 levels simulated Miocene climate shows a reduced polar amplification, linked to a breakdown of seasonality in the Arctic Ocean. A pronounced warming in boreal fall is detected for a CO 2 increase from 280–450 ppm, in comparison to weaker warming for CO 2 changes from 450–720 ppm. Moreover, a pronounced warming in winter is detected for a CO 2 increase from 450–720 ppm, in contrast to a moderate summer temperature increase, which is accompanied by a strong sea-ice concentration decline and enhanced moisture availability promotes cloud formation in summer. As a consequence planetary albedo increases and dampens the temperature response to CO 2 forcing at a warmer Miocene background climate.